Predefined-Time Event-Triggered Adaptive Fuzzy Formation Control for Nonholonomic Multirobot Systems - Li, Kewen; Dong, Shijie (IEEE transactions on fuzzy systems, 2024)
In this article, the problem of predefined-time event-triggered (PTET) robust adaptive fuzzy formation control is studied for nonholonomic multirobot systems (NMRSs) subject to multiple constraints and dead-zones. The adaptive estimation technique and fuzzy logic systems are used to identify nonlinear NMRSs with uncertain dynamics. By combining prescribed performance control method and introducing universal barrier functions, the transient and steady-state performances of the NMRSs are guaranteed, thereby further achieving collision avoidance and connectivity maintenance. On this basis, in order to achieve predefined-time convergence of formation errors and reduce the transmission frequency of control signals from controller to actuator for each robot with input dead-zones, a novel adaptive fuzzy robust PTET formation control strategy is further proposed by introducing predefined-time stability theory and designed trigger mechanism. It can avoid significant resource waste during rapid tracking processes, ensure the nonlinear NMRSs are predefined-time stable and all signals are bounded, which can be proved by constructing the barrier Lyapunov functions. In the end, the simulation studies are carried out to show the efficacy of the developed adaptive PTET formation control strategy.